An Impact Analysis Of The Stunting Handling Program In Anambas Islands Regency In 2023 - Rahayu Rahayu; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Abstract. In 2013, the prevalence of stunting in Indonesia reached 34.1% and only decreased to 31% in 2022. Therefore, the Indonesian Government is targeting a reduction in the prevalence of stunting to 14% in 2024 through national policies and various programs at various levels of government. One of the areas that has a program to accelerate the reduction of stunting is the Anambas Islands Regency which has a stunting prevalence of 21.7% in 2021. This study aims to determine the impact of the implementation of the prevention and acceleration program for reducing stunting in the Anambas Islands Regency. This study is a qualitative study conducted at the Tarempa Health Center and the Siantan Selatan Health Center. Information in this study was obtained from three Key Informants (Head of the Health, Population Control, and Family Planning Office, Head of the Siantan Selatan Health Center, and Tarempa Health Center Posyandu Cadres) and four Ordinary Informants (mothers of stunted children). Data collection in this study was carried out through in-depth interviews and analyzed by triangulation and matching with secondary data. In addition, communication between implementing actors is carried out routinely through both face-to-face and online, implementation resources are well available, all implementing actors have good dispositions, and have a clear bureaucratic structure. It can be concluded that the implementation of prevention and acceleration of stunting reduction is running well and has succeeded in reducing the prevalence of stunting in Anambas Islands Regency.